River Terraces Mapping and Assessment of Their Characteristics along the Middle Section of the Madi River, Western Nepal, Lesser Himalaya - Dhakal, Ashok; Lamsal, Sunil; Paudyal, Kabi Raj (Journal of Nepal Hydrogeological Association, 2025)
The Madi River, a major tributary of the Sapta Gandaki River in west-central Nepal, exhibits well-developed fluvial terraces that provide insights into Late Quaternary landscape evolution in the Lesser Himalaya. This study focuses on the middle section of the Madi River, from Duipiple to Rudi Dhoban, where three distinct terrace levels higher, middle, and lower were identified along both banks. Six representative sites (Mohoriyatar, Dihi, Dargau, Syastri, Bhatbesi, and Tallobesi) were examined from south to north. The higher terrace, measuring approximately 80 m in height and 46 m in width relative to the modern channel, is composed predominantly of large boulders of gneiss, quartzite, garnet schist, and met sandstone, and is interpreted as the product of glaciofluvial deposition. The middle terrace is widely distributed at around 40 m above the active channel and extends up to 90 m in width, consisting of unsorted, consolidated boulders, cobbles, pebbles, and granules derived from gneiss, quartzite, schist, phyllite, and metasandstone. The lower terrace is the youngest unit, lies ~20 m above the modern river and extends ~120 m in width, containing rounded to sub-rounded sediments sourced from the Higher and Lesser Himalaya. Tributary inputs contribute angular clasts of phyllite and met sandstone to the middle and lower terraces. Sediment provenance analysis indicates transport from both the Higher Himalaya and Lesser Himalaya zones. The terrace stratigraphy and sedimentology suggest that the higher terrace formed under glaciofluvial conditions, while the middle and lower terraces are products of purely fluvial processes.